Solutions to Elementary Education Constraints through ICT-Based Learning Media in the Era of Society 5.0. - susanti, lilik; Julia, Rahma (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2025)
This study aims to identify and describe solutions to various challenges faced in elementary education, particularly at SD N 02 Sripendowo, through the utilization of Information and Communication Technology (ICT)-based learning media in the era of Society 5.0. This era demands the integration of advanced technology with human needs, including in the education sector. A descriptive qualitative method was employed in this research, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the main challenges in elementary education include limited learning facilities, low digital literacy among teachers and students, and a lack of innovation in instructional methods. The use of ICT-based learning media has proven to be an effective solution in overcoming these obstacles, such as through the implementation of interactive educational videos, digital learning platforms, and regular training for teachers in technology use. Thus, the integration of ICT in the learning process at SD N 02 Sripendowo positively contributes to the improvement of learning quality and prepares students to face the challenges of the Society 5.0 era.